Amdahl's Law. (Computer (00189162), 2008)
The article focuses on Amdahl's law, a computer science formula developed by scientist Gene Amdahl regarding the speedup of computation processes. Amdahl's law argues that advances in single processor computing can result in large increases in computing capabilities. Recent research argues that the formula has less applicability to powerful parallel computers.